Association between molecular markers located in 4q and non-syndromic cleft lip and palate in a Chilean population - Alhuay, Joel (2022)
The objective of this investigation is to test the hypothesis of the possible association of one or more microsatellites located on 425-4933 with NSCLP. In this study a sample of 51 extended pedigrees were analyzed. From these pedigrees a sample of 51 caseparents trios was obtained. A novel genetic analysis was carried out using the Extended Transmission Disequilibrium Test (ETDT). Also a case control study was carried out with the 51 probands of the case-parents trios plus a sample of 94 controls of the Chilean population to test if differences were observed resulting from the methods used for the association studies. Microsatellites D4S1570, D4S1615, FGA, UCP1 and D4S1597 located in 4q were analyzed. The polymerase chain reaction (PCR) was used for analysis of DNA. Forward primers were marked with fluorescent-dye-label. Electrophoresis and analyses were carried out in an ABI PRISM 377 automatic sequencer. In the case-control study, only FGA was in H-W equilibrium in controls, whereas FGA, D4S1570 y D4S1597 were in H-W equilibrium in cases. These results imply that a case control study does not represent an adequate procedure to carry out an association study between the aforementioned microsatellites and NSCLP. In order to obviate this problem the ETDT program was used. From all of the analyzed microsatellites, D4S1570, UCP1 and D4S1597 presented significant allele wise association in those case-parents trios to multiplex families. This result suggests that these microsatellites would be located close to one or more candidate genes for this malformation in 4q24-4q31.